Planar cell polarity coordination in a cnidarian embryo provides clues to animal body axis evolution - Julie Uveira; Antoine Donati; Marvin Léria; Marion Lechable; François Lahaye; Christine Vesque; Evelyn Houliston; Tsuyoshi Momose (eLife)
Body axis specification is a crucial event in animal embryogenesis and was an essential evolutionary innovation for founding the animal kingdom. This process involves two distinct components that coordinate to establish the spatial organisation of the embryo: initiation of cascades of regionalised gene expression and orientation of morphogenetic processes such as body elongation. Intense interest in the first component has revealed Wnt/β-catenin signalling as ancestrally responsible for initiating regional gene expression, but the evolutionary origin of oriented morphogenesis has received little attention. Here, by addressing the cell and morphological basis of body axis development in embryos of the cnidarian Clytia hemisphaerica, we have uncovered a simple and likely ancestral coordination mechanism between Wnt/β-catenin signalling and directed morphogenesis. We show that the ligand Wnt3, known to initiate oral gene expression via localised Wnt/β-catenin pathway activation, also has a key β-catenin-independent role in globally orienting planar cell polarity (PCP) to direct morphogenesis along the oral-aboral axis. This PCP orientation occurs in two distinct steps: local orientation by Wnt3 and global propagation by conserved core PCP protein interactions along the body axis. From these findings, we propose novel scenarios for PCP-driven symmetry-breaking underlying the emergence of the animal body plan.